Aid and Growth: What Does the Cross-Country Evidence Really Show? - Rajan, Raghuram G.; Subramanian, Arvind (The Review of Economics and Statistics, 2008)
We examine the effects of aid on growth in cross-sectional and panel data—after correcting for the possible bias that poorer (or stronger) growth may draw aid contributions to recipient countries. Even after this correction, we find little robust evidence of a positive (or negative) relationship between aid inflows into a country and its economic growth. We also find no evidence that aid works better in better policy or geographical environments, or that certain forms of aid work better than others. Our findings suggest that for aid to be effective in the future, the aid apparatus will have to be rethought.